Corrosion of Ni-Ti Rotary Instruments: A Review - Zahed Mohammadi; Jun-Ichiro Kinoshita; Atsufumi Manabe; Mikihiro Kobayashi; Sousan Shalavi; Hamid Jafarzadeh (Journal of Dental Materials and Techniques, 2019)
The nickel-titanium (Ni-Ti) alloys used in endodontics contain 56% Ni and 44% Ti. The 2 unique features related to clinical dentistry (i.e., shape memory effect and superelasticity) are due to the transition from austenite to martensite in Ni-Ti alloy. When a superelastic Ni-Ti alloy undergoes a low tensile loading, normal elastic behavior occurs. In fact, at higher tensile loads, the elastic stress may reach a level at which there is extended horizontal region of elastic strain. The shape-memory property of Ni-Ti is derived from an atomic arrangement different from that of alloys like stainless steel. The purpose of this paper was to review the unique features of this alloy and mechanism of corrosion.